Implementing an undergraduate learning assistant model to foster engagement and professional development in microbiology courses - Katriana A. Popichak; Paige E. Gruber; Erica L. Suchman; Jennifer L. McLean (Journal of Microbiology & Biology Education)
ABSTRACT Integrating undergraduate learning assistants (ULAs) into high-enrollment science, technology, engineering, and mathematics (STEM) courses has been shown to enhance student engagement, yet the impact on ULAs themselves remains underexplored. This manuscript presents a field-tested framework for implementing and sustaining a structured ULA program in a General Microbiology course, offering a replicable model for educators seeking to enhance student learning and ULA professional development (PD). Over the past decade, this program has been refined to provide structured mentorship, leadership opportunities, and active involvement in both in-class and out-of-class activities. The ULA program fosters student engagement by incorporating active learning strategies such as iClicker questions, group exams, and flipped classroom exercises, ensuring a collaborative and supportive learning environment. At the same time, ULAs develop critical skills in communication, teamwork, assessment, and pedagogy, which align with key PD objectives. Faculty observations indicate that students who engage with ULAs exhibit increased conceptual understanding, participation, and peer collaboration. Likewise, anonymous ULA feedback highlights significant growth in teaching confidence, leadership, and academic preparedness. This article serves as a practical guide for educators by outlining a structured, adaptable curriculum, detailing strategies for faculty mentoring, and providing implementation best practices. While formal assessment of learning gains is ongoing, preliminary findings suggest that ULAs serve as valuable instructional assets while simultaneously benefiting from the experience. This dual impact underscores the importance of structured ULA programs in enhancing undergraduate education and preparing future educators and professionals.